Effect of Momordica charantia on the removal of arsenic from different organs of arsenic-treated rat - Akhter, Shakila; Misbahuddin, Mir (Bangabandhu Sheikh Mujib Medical University Journal, 2019)
The present study was designed to examine the effect of Momordica charantia ethanol extract on the removal of arsenic from different organs of the arsenic-loaded rat. The rats (n=30) were divided into 5 groups: a) control, b) arsenic-treated (200 µg/L), c) extract-treated (50 mg/day), and d) arsenic plus extract-treated (50 or 200 mg/kg). The rats were sacrificed on day 61. The study revealed that there were significant accumulation of arsenic in the liver, kidneys, intestine and skin. On the other hand, there was significant decrease in glutathione level in the liver. The administration of extract significantly decreased the amount of arsenic in all the organs tested and increased the glutathione level significantly in the liver. The maximum reduction of arsenic was found in skin (100%), liver (91.2%), intestine (89.2%) and kidney (83.1%). The maximum elevation of glutathione in liver was 48.3%. In conclusion, M. charantia reduces the arsenic level from different organs of the arsenic-loaded rat.